The Development of Venture Capital Industry and the Role of Government in Korea: Venture Boom vs. Post-boom - Lee, Su Il (KDI Journal of Economic Policy, 2008)
This paper evaluates the role of Korean government in the venture capital industry, in particular in the stages of fund-raising and venture investment. Utilizing data from Korean Venture Capital Association (KVCA), the analysis is conducted for the venture boom and post-boom periods separately. Empirical results show that the government played a significant role in the fund-raising stage in both venture boom and post-boom periods. When it comes to the investment stage, however, the empirical results indicate that the government did not accomplish expected roles. In particular, the government failed to induce investments in the outside funds of which the government had a larger stake toward early-staged firms and guide common stock investments during the venture boom period. The empirical outcomes also show that the government has not properly increased venture investments on high-tech industries during the post-boom period. This paper argues tentative reasons why the policy failures were observed in relation to the policy implications and provide several pieces of supporting evidence.